Pengaruh Harga Emas Dan Nilai Tukar Rupiah Dolar Di Indonesia Terhadap Indeks Harga Saham Gabungan (ihsg) 2020 - 2022 - Zulkarnaen, Fadillah Hafizh; Santoso, Teguh Iman (eProceedings of Management, 2024)
Entering 2020, the global economy is facing great pressure due to the COVID-19 pandemic, which has causedinstability in various countries. The impact can be seen on capital markets and currency exchange rates. Fluctuationsin the